From Caricature to Critique: Satirical Portraits of the Upper Class in Martin Chuzzlewit (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Attempts to study the description of caricature to criticism: satirical portraits of the upper class in Martin Chuzzlewit its structure have been undertaken for a long time. At the same time, research thought sometimes moved away, sometimes approached the understanding of the essence of this phenomenon. This is explained by only two circumstances. The first of them is that the phenomenon itself, called the novel, was formed historically, the genre is the memory of literature. It was constantly changing and modifying, enriched with new features. This prevented researchers from capturing and designating its unchanging contours, i.e. some stable, repeating features that are now commonly called typological. The second circumstance depends to a greater extent on the methodological positions of researchers, which are also constantly changing and updating, sometimes promoting, sometimes hindering scientific knowledge.